The Relationship between Interpersonal and Intrapersonal Intelligences and Classroom Management Strategies among Instructors of English for Medical Sciences - Mavadat Saidi; Zohreh Bayatshahbazi (Mashhad University of Medical Sciences, 2021)
Background: The current study strived to unfold the relationship between interpersonal and intrapersonal intelligence types and classroom management strategies among the instructors of teaching English toward the students of medical sciences. The study further tried to see if there was any significant difference between language and content instructors in terms of their classroom management strategies in their classes.Methods: A convenient sample of 80 EAP instructors from state universities of Tehran, Tabriz, Isfahan, and Mashhad provided responses to the excerpted items related to personal intelligences from McKenzie's Multiple Intelligences Questionnaire and Behavior and Instructional Management Scale (BIMS). A Pearson product-moment correlation test was run to determine the possible link between the participants' personal intelligences and their classroom management strategies. Moreover, an independent sample t-test was used to find out the possible difference between language and content instructors in terms of their classroom management strategies.Results: The results revealed a significant relationship between the instructors' interpersonal and intrapersonal intelligences and their classroom management strategies. Furthermore, a significant difference was found between language and content instructors in terms of their classroom management approaches in English for the students of medical science courses.Conclusion: The findings can raise the EAP instructors' consciousness to enhance their interpersonal and intrapersonal intelligence types in order to improve and promote their classroom management strategies. In addition, the results may enhance the policymakers' perception of the required considerations for in-service teacher training courses of English for medical science instructors.